Challenges in engaging students with learning disabilities in food industry - Nik Othman, Nik Norlaili Jamilah; Mohd Kamaruzaman, Fathiyah; Rasul, Mohamad Sattar (Institute of Advanced Engineering and Science, 2024)
Students with learning disabilities (SLD) with potential for independent living and economic contribution can thrive by participating in technical and vocational programs tailored to the food industry. To ensure that SLDs do not lag behind a thorough comprehension of the challenges they confront is imperative for all stakeholders, including parents, instructors, and the government. Thus, the study investigated the challenges of engaging in vocational education for SLD. This study utilized systematic literature review (SLR) methodology, which synthesizes research findings to generate new insights and understandings. This study identified six challenges that students with learning disabilities must overcome before entering the workforce. The challenges are i) employment difficulties; ii) lack of resilience; iii) mismatch between special educational institution and industry needs; iv) curriculum deficiency for students with learning disabilities; v) lack of parental involvement and employer support; and vi) insufficient understanding of job descriptions in the food industry. Findings from this study provide valuable insights into the challenges faced by SLDs seeking to be part of the food industry. This knowledge can facilitate further research to develop job profiles that align with their unique abilities, ultimately fostering their success in careers and enriching their lives.